Analysis of pregnancy outcomes in women with type 1 diabetes mellitus diagnosed before pregnancy: a systematic review (Research, Society and Development, 2021)
Type 1 Diabetes mellitus affects men and women in different age groups around the world. This condition is of special concern when associated with pregnancy as it tends to cause several complications for mother and fetus during pregnancy, the time of delivery and after birth. This article aims to study the outcome of pregnancies in women with type 1 diabetes through a systematic review. A systematic review of observational studies referring to pregnancy in diabetics, type 1 diabetes and maternal-fetal complications was carried out based on articles from the PubMed and Bireme databases. Data were extracted from the 19 articles included. The observed data that most attracted attention were related to the occurrence of pre-eclampsia and/or preterm birth and the birth of large-for-gestational-age fetuses. Similar observations were made for other important items (eg, Apgar score, newborn weight, diabetes treatment). It was concluded, then, that an ideal glycemic control is essential and effective to prevent the occurrence of unfavorable pregnancy outcomes.